(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The guiding nature of the objectives and the close relationship between them and the contents, methods, means and evaluation, as essential components of this formative process, as well as the philosophical, sociological, psychological and pedagogical foundations are the current starting point of Education in Cuba. This research aims to guide teachers, through argumentation and demonstration, the methodological aspects for the achievement of the didactic-methodological structuring of the class, so that it contributes to the preparation for the execution of the teaching-learning process developer of the students of the first year of the Bachelor of Education career Chemistry at the University of Granma. Theoretical, empirical and statistical methods are used to carry out the research. Among the theorists: analysis-synthesis, deduction-induction, among the empirical: observation, survey, and documentary analysis. Of the mathematical statistician: techniques of descriptive statistics and percentage calculation. The novelty of the research lies in the methodological treatment of the conference on chemical equilibrium from the foundations of the developer didactics for the integration of the knowledge acquired with a scientific, systemic, integrative and developer approach of the teaching-learning process as well as the development of the skills and values that students should apply in their profession life.